1985
DOI: 10.1520/jfs11044j
|View full text |Cite
|
Sign up to set email alerts
|

The Isolation and Identification of Precursors and Reaction Products in the Clandestine Manufacture of Methaqualone and Mecloqualone

Abstract: Abuse of the hypnotic quinazolinone is well recognized and increasing. Clandestine laboratories producing methaqualone (2-methyl-3-othro-tolyl-4(3H) quinazolinone) and mecloqualone (2-methyl-3-othro-chlorophenyl-4(3H) quinazolinone) have been discovered throughout the United States. These laboratories utilize one of many synthesis routes to produce the illicit quinazolinone. Frequently, the clandestine chemist has little, if any, formal education in chemistry; does not keep notes; and does not label flasks and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The synthesis of methaqualone and related quinazolinones is not difficult (Angelos & Meyers 1985;Soliman et al 1978) and obviates the need for exogenous sources of methaqualone. Two homologues of methaqualone (mecloqualone, nitromethaqualone) which have been in clinical use in Europe are reported to be synthesised by clandestine laboratories in the United States (Daenens & Van Boven 1976Ĩ ntoxication is typified by ataxia and lethargy, although initially a period of disinhibited stimulation may be noted.…”
Section: Methaqualone Derivativesmentioning
confidence: 99%
“…The synthesis of methaqualone and related quinazolinones is not difficult (Angelos & Meyers 1985;Soliman et al 1978) and obviates the need for exogenous sources of methaqualone. Two homologues of methaqualone (mecloqualone, nitromethaqualone) which have been in clinical use in Europe are reported to be synthesised by clandestine laboratories in the United States (Daenens & Van Boven 1976Ĩ ntoxication is typified by ataxia and lethargy, although initially a period of disinhibited stimulation may be noted.…”
Section: Methaqualone Derivativesmentioning
confidence: 99%
“…They holds a broad range of biological activity including analgesic, antimalarial, anti‐inflammatory, anti‐convulsant, antimycobacterial, anticancer, antihypertensive and anticancer activities . For example, quinazolinone drug, methaqualone A was widely used as a sedative‐hypnotic agent . Additionally, some of these compounds like B and C , used as a kinase and dihydrofolate reductase inhibitors .…”
Section: Introductionmentioning
confidence: 99%
“…[1] For example, quinazolinone drug, methaqualone A was widely used as a sedative-hypnotic agent. [2] Additionally, some of these compounds like B and C, used as a kinase and dihydrofolate reductase inhibitors. [3] Proquazone D and Fluproquazone E used in the treatment of rheumatoid arthritis by the inhibition of prostaglandin synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of methaqualone I ( Figure 1 ) as a sedative hypnotic [ 19 , 20 ], the search for new anticonvulsant drugs with reduced toxicity and fewer side effects has been continuous. Our literature survey revealed that replacement of the methyl group by some other functionalities such as alkylthiomethyl or alkyloxymethyl groups reportedly yielded structural analogues which retained the anticonvulsant activity [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%